Intelligent Travel Bot using Wide and Deep Learning - Rele, Siddhant; Furniturewala, Danish Ali; Raulo, Sagar; Shah, Neepa (International Journal of Computer Sciences and Engineering, 2018)
The usual approach of planning a trip involves a serious of tedious tasks. The manual way is to book through a travel company, which will give you an itinerary for your trip and the costs involved, another way is to book through an online website, where you can pick a place, look for hotel, book a room and then make travel arrangements to your desired destination. The process involved is time consuming and involves looking through various booking websites to find the best bang for your buck. We propose a solution which will make this process as smooth as possible through the use of an interactive travel bot deployed on social media platforms. In this travel bot, a user enters a query asking for a place to stay in a location. The travel bot then constructs a persona based on transactional history of the user, for example, hotels that the user has shown interest in previously. Using this persona and a wide and deep neural network, personalized recommendations are generated by the travel bot.